1988
DOI: 10.1177/106002808802201102
|View full text |Cite
|
Sign up to set email alerts
|

Review of Diclofenac and Evaluation of its Place in Therapy as a Nonsteroidal Antiinflammatory Agent

Abstract: Diclofenac sodium is a nonsteroidal antiinflammatory drug (NSAID) that has been used in 120 countries since its introduction in Japan in 1974. It is currently the eighth largest-selling drug and the most frequently used NSAID in the world. Diclofenac, a phenylacetic acid derivative, is a potent inhibitor of cyclooxygenase enzyme activity, and may also interact with the lipoxygenase enzyme pathway, and with the release and reuptake of arachidonic acid. Diclofenac is almost completely absorbed, highly protein-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 44 publications
(4 reference statements)
3
73
0
1
Order By: Relevance
“…When efficacy remains the same, however, there is a decrease in potency. Diclofenac is reported to have a potency greater than all the NSAIDs tested (Skoutakis et al, 1988), which is in agreement with our observations. In fact, diclofenac was so potent that the ED 50 in animals given chronic THC was lethal in our chronic vehicle (1:1:18) animals.…”
Section: Discussionsupporting
confidence: 83%
“…When efficacy remains the same, however, there is a decrease in potency. Diclofenac is reported to have a potency greater than all the NSAIDs tested (Skoutakis et al, 1988), which is in agreement with our observations. In fact, diclofenac was so potent that the ED 50 in animals given chronic THC was lethal in our chronic vehicle (1:1:18) animals.…”
Section: Discussionsupporting
confidence: 83%
“…These phenotypes share some common features with human inflammatory disorders, and thus, the Tg(hsp70: m il-1b_eGFP;lyz:DsRed2) hkz10t;nz50 transgenic line could be used as an animal model for developing new therapeutic strategies for the treatment and prevention of human inflammatory disorders. To provide proofof concept evidence to support such a notion, we tested whether the treatment of Tg(hsp70: m il-1b_eGFP;lyz:DsRed2)hkz10t; nz50 embryos with diclofenac and dexamethasone, two antiinflammatory drugs commonly used for clinical treatment of human inflammatory disorders (27,53,54), could reduce the inflammation. Result showed that anti-inflammatory treatment with diclofenac and dexamethasone significantly reduced the number of abnormal distributed neutrophils in heat shock-treated Tg(hsp70: m il-1b_eGFP;lyz:DsRed2)hkz10t;nz50 embryos (Fig.…”
Section: Overexpression Of Il-1b Induces a Systemic Inflammation In Zmentioning
confidence: 99%
“…Diclofenac, a non-steroidal anti-inflammatory drug (NSAID), is commonly employed in the treatment and/or management of rheumatoid arthritis, osteo-arthritis and ankylosing spondylitis (Eddy and Leimback, 1953;Siraux, 1977) and for its anti-inflammatory and analgesic effects (Brooks et al, 1980). Diclofenac reduces inflammation, swelling and arthritic pain by inhibiting prostaglandins synthesis and/or production (Skoutakis et al, 1988;Todd and Sorkin, 1988;Small, 1989). It is known that non-steroidal anti-inflammatory drugs usually do not increase the pain threshold in normal tissues, whereas local anesthetics and narcotics do (Ferreira et al, 1978).…”
Section: Discussionmentioning
confidence: 99%